THE APLICATION OF DIGITAL STORYTELLING IN TEACHING SPEAKING - Ircham Asrori (Department of English Education, Universitas Panca Sakti Bekasi, 2021)
The first aim of this study was to explore the application of digital storytelling in teaching speaking at the students of state senior high school No 1 Pelepat Kabupaten Bungo. Second, it aims to explore the benefits of digital storytelling in contributing to speaking class. Third, it aims to explore the participants’ perception. This study used qualitative method. The data collection technique used was observation, interview, and audiovisual material. The participants were an English teacher and six of twenty-four students of eleventh grade. The sampling technique used was purposive sampling. The data was analyzed qualitatively by using triangulation. The first finding was digital storytelling use in teaching speaking as in the following procedures: writing the story, recording the story, collecting related pictures, combining (recording and relevant images), and the last step was presenting and evaluating. The second findings was the application of digital storytelling had some benefits such as it contributed to practice and improve students’ speaking skill, the students be familiar with the pronunciations, self-confidence, and evaluated or assessed students’ improvement in speaking skill. The last finding of this study showed that the digital storytelling use in teaching speaking provided participants to have positive and negative perception; for example, high motivation in learning, easy, interesting, and enjoyable media, while for negative perceptions were difficulties in editing, limited time, and lack of related images.